The Challenges Faced by the Student-Teachers in Teaching Online English Learning - Fitriana, Dina (Budapest International Research and Critics University, 2022)
This research describes the challenges faced by student-teachers in teaching online English. The study aims to explain student-teacher teachers' experiences relating to classroom management during the student-teacher teachers' teaching practicum in junior high school. The research used the descriptive qualitative method. A semi-structured interview and online questionnaire were conducted with four student-teacher teachers to find their responses relating to their challenges, how they faced them, and the suggestions they gave for improving classroom management through an online classroom. The findings showed that the unpreparedness of student-teacher teachers and students during the transition from the offline classroom to online learning was a challenge in managing the online class.